ANALISIS KEMAMPUAN METAKOGNISI SISWA TERHADAP MATERI BANGUN RUANG DI SD - Lenny Gusti Anggraini; Nirwana Anas (Universitas Negeri Medan, 2019)
This study aims to analyze the extent to which the metacognition abilities of fifth grade elementary school students in mathematics subject to material in space. This type of research is descriptive qualitative, the subjects in the study were elementary school students class V-b, amounting to 31 people. Data was collected using a questionnaire that refers to the rubric Metacognitive Awareness Inventory (MAI) compiled by Schraw and Dennison (1994) (in the articel of George, M. Harrison, et al. (2017). Analysis (MAI) is divided into two abilities namely cognitive ability and cognitive regulation skills and developed in eight indicators namely declarative knowledge, procedural knowledge, conditional knowledge, information management strategy planning, planning, monitoring comprehension, error correction and evaluation strategies totaling 52 items.The results showed that metacognition skills in elementary school students in grade V shows that the ability of knowledge of cognition 80% and regulation of cognition 81% with this can be said to be very related.This relationship can be seen from the average of the two that are almost the same.In addition, these results indicate that elementary school students in grade V already have the metacognition abilities used in completing various problems in p process of learning to build space.Keywords: Build Space, Metacognition, Metacognition of knowledge